Population dynamics of the edible rock oyster Saccostrea cucullata (Born, 1778) along the south-west coast of India - Yambem Tenjing, S. (Indian Journal of Fisheries, 2020)
For the management of molluscan stocks, knowledge of various population parameters and exploitation level of the population are needed. The present study assessed the population dynamics on the rock oyster Saccostrea cucullata (Born, 1778) in Karnataka State, south India. The specimens of S. cucullata were collected from Baindur rocky beach at monthly intervals from June 2010 to May 2011. Asymptotic length (Lâˆž) estimated was Â 57.8 mm and growth coefficient (K) was estimated at 1.4 year-1. The sizes attained were 45.30, 54.72 and 57.04 mm at the end of first, second and third years of age, respectively. Total mortality (Z) was 5.24 year-1. Natural mortality (M) and fishing mortality (F) were 1.40 and 3.84 year-1 respectively. The life span of S. cucullata was estimated as 2.5 years approximately. Exploitation level (E) was computed as 0.73, indicating that the fishery of S. cucullata in the coastal waters of Karnataka Is overexploited. Keywords: Age, Exploitation, Growth, Karnataka, Mortality, Recruitment, Â Rock oyster, Saccostrea cucullata